دور الثقافة التنظيمية في الحد من مقاومة العاملين للتغيير دراسة ميدانية على العاملين في مجلس مدينة اللاذقية - قاسم سامر (Tishreen University Journal- Economic and Legal Sciences Series, 2015)
يهدف البحث إلى التعرف على دور الثقافة التنظيمية في الحد من مقاومة العاملين للتغيير من خلال دراسة العلاقة بين أبعاد الثقافة التنظيمية, وأسباب مقاومة العاملين للتغيير في مجلس مدينة اللاذقية. ولتحقيق أهداف البحث تمّ تصميم استبانه, وتوزيعها على (343) عاملاً في مجلس مدينة اللاذقية, حيث أعيد منها (315) استمارة كاملة وصالحة للتحليل الإحصائي, وبنسبة استجابة بلغت (91.84%), وبالاعتماد على الانحدار المتعدد تمّ التوصل إلى النتائج الآتية: 1- هناك علاقة عكسية متينة ودالة إحصائياً بين عناصر بعد الاحتواء والترابط المتمثلة بـ (التمكين, تطوير العاملين, العمل الجماعي, المشاركة), والحد من مقاومة العاملين للتغيير, أي كلما توفرت عناصر بعد الاحتواء والترابط أدى ذلك إلى انخفاض أسباب مقاومة العاملين للتغيير. 2- هناك علاقة عكسية متينة ودالة إحصائياً بين عناصر بعد الاتساق والتجانس المتمثلة بـ (القيم الجوهرية, الاتفاق, التنسيق والتكامل), والحد من مقاومة العاملين للتغيير, أي كلما توفرت عناصر بعد الاتساق والتجانس أدى ذلك إلى انخفاض أسباب مقاومة العاملين للتغيير. 3- هناك علاقة عكسية ومتينة ودالة إحصائياً بين عناصر البعد الإنساني المتمثلة بـ (الاحترام والتقدير, العدالة, تشجيع الإنجاز, الرعاية الاجتماعية), والحد من مقاومة العاملين للتغيير, أي كلما توفرت عناصر البعد الإنساني أدى ذلك إلى انخفاض أسباب مقاومة العاملين للتغيير. 4- هناك علاقة عكسية ومتينة ودالة إحصائياً بين عناصر بعد المناخ التنظيمي المتمثلة بـ (الممارسات الإدارية, المكافآت, الاتصالات, نظام الإشراف), والحد من مقاومة العاملين للتغيير, أي كلما توفرت عناصر بعد المناخ التنظيمي أدى ذلك إلى انخفاض أسباب مقاومة العاملين للتغيير. The research aims to identify the role of organizational culture in reducing resistance to change of the employees through a study of the relationship between the dimensions of the organizational culture, and the reasons of resistance change by employees working in Lattakia City Council. To achieve the objectives of the research, a questionnaire was designed and distributed to (343) employees in Lattakia City Council, (315) questionnaire were complete and valid for statistical analysis, with a response rate of (91.84%). Relying on multiple regression, the following results were reached: 1. There is a strong inverse relationship which is statistically significant between the elements after the containment and interdependence of (empowerment, staff development, teamwork and participation), and a reeducation of the resistance of workers to change, wherever after containment and coherence elements are available, there is a decline in the causes resistance of workers to change. 2. There is strong inverse relationship that is statistically significant between the elements after the consistency and uniformity of working (core values​​, agreement, coordination and integration), and a reduction of resistance workers to change, i.e. when elements after consistency and homogeneity are availed, they lead to a decline in the causes of workers resistance to change. 3. There is strong inverse relationship which is statistically significant between the elements of the human aspects (respect and appreciation, justice, encouragement achievement, and social welfare), and the reeducation of workers resistance to change, i.e., whenever there are elements of the human aspects, there is a decline of the causes of workers resistance to change. 4. There is strong inverse relationship which is statistically significant between the elements after the organizational climate of (administrative practices, rewards, communications, and surveillance system), and the reduction of workers resistance to change, i.e., wherever after the organizational climate elements are available, there is a decline in the causes of workers resistance to change.